Analisa Pengendalian Kualitas pada Home Industri Makanan - Sopyan Saori; Laila Hamidah; Nur Azmi; Aldi Rouf Ramdan; Muhammad Reza (Syntax Idea, 2021)
The purpose of this research is to explain whether quality control in MSMEs Mochi Bakat Jaya is able to provide satisfaction for consumers and can be superior to competitors and identify the factors that cause damage to the uk prodUMKM Mochi Bakat Jaya. This research method uses primary data which is then analyzed based on check sheet and made pareto diagram and causal diagram. The results showed that the failed product in MSMEs Mochi Bakat Jaya is the income of inappropriate peanuts by 53% and the dough is too hard by 43%. Fthe lead actor who causes damage or incompatibilityto theproduct is human and method. The number of mochi products produced by MSMEs Mochi Bakat Jaya during November 2020 amounted to 2,391 and the total number of failed or defective products was 150. By analyzing using pareto diagrams, the main factor that most affects the damage or incompatibility of mochi products is the incompatibility of 53% of the total number of failed or defective products. Followed by a dough too hard by 43%. Furthermore, by using a causal diagram it can be concluded that the main factors that cause damage or incompatibility in mochi products are human and method.